Geospatial Assessment of Limestone Mining-Induced Land Use Change in Okpella, Edo State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed limestone mining-induced land use and land cover change and its implications for agricultural land loss in Okpella, Edo State, Nigeria. A mixed-methods approach was adopted, integrating remote sensing, Geographic Information System (GIS) analysis, questionnaire surveys, and focus group discussions. Multi-temporal satellite images for 2002, 2014, and 2024 were classified using a supervised Random Forest algorithm to quantify land use changes, while descriptive and inferential statistics were used to analyze socio-economic data obtained from 400 respondents. Results indicate substantial land transformation over the study period. Agricultural land declined from 229.17 km² in 2002 to 104.29 km² in 2024, while mining areas increased from 0.36 km² to 9.52 km². Built-up areas also expanded gradually, while vegetation cover decreased consistently. Classification accuracy assessment showed strong reliability, with overall accuracies ranging from 88.89% to 92.86% and Kappa coefficients between 0.846 and 0.899. Regression analysis revealed a statistically significant relationship between limestone mining and land use change (R² = 0.387, p < 0.05), indicating mining as a key driver of spatial transformation in the study area. Respondents’ perceptions further confirmed that mining activities negatively affect soil quality, crop yields, and agricultural practices. The study concludes that limestone mining has significantly contributed to agricultural land loss and landscape transformation in Okpella. Sustainable land management strategies, stricter environmental regulation, and reclamation policies are recommended to balance mineral extraction with agricultural sustainability.